(untitled) (Philological Studies, 2019)
This article presents analysis of Russian-language folklore songs of Udorsky Komi. The texts where recorded on the territory of the Udorsky district of Komi Republic in 1988–1999 and stored in Folklore archive of the Syktyvkar State University of Pitirim Sorokin. The archive contains in total 24 plots recorded in 63 variants, the repertoire includes round dance songs, dance tunes and pripevka (short songs). Mezen and Pinezhye had big influence on formation of song tradition of Udora. Udorsky ethno-regional tradition contains both popular and rare Russian folk lyrics. The comparison with song texts from the Russian North shows high degree of their similarity (actually – identity). In the same time, udorsky variants of Russian songs have interesting contaminations of motives, which appeared as a result of long functioning in Komi culture. However, the influence of the Komi tradition is not manifested at the language level: almost all folklore songs were performed and recorded without significant language distortions and adaptations.